Critical Analysis of the Lyrics of the Song "Kenakalan Remaja di Era Informatika" By Efek Rumah Kaca - Sesilia Maharani; Khaerudin Imawan (Jurnal Bisnis dan Komunikasi Digital, 2025)
The rapid development of information technology has changed the patterns of communication among teenagers in the digital space and given rise to new forms of juvenile delinquency, one of which is related to the dissemination of pornographic content. This social phenomenon has led to the creation of the song “Kenakalan Remaja di Era Informatika” by Efek Rumah Kaca, which represents social criticism of the ethical crisis among teenagers in their use of digital technology. This study aims to analyze how text structure, social cognition, and social context construct social criticism discourse in the song's lyrics, as well as to identify the forms of criticism conveyed. This study uses a descriptive qualitative approach with Teun A. Van Djik's Critical Discourse Analysis (CDA) model. Data was obtained through song lyric analysis and interviews with informants selected purposively. The results show that this song builds social criticism through the representation of youth behavior in the digital realm, constructed as a form of ethical deviation, particularly in digital pornography. Through the relationship between the text structure, the social cognition of the songwriter, and the social context of the time, this song functions not only as a musical work but also as a discourse of social criticism that reflects the reality and concerns of society regarding the morality of adolescents in the digital space.